What Can Quantum Physicists Tell Educators? - Dündar-Coecke, Selma (Journal of Interdisciplinary Studies in Education, 2021)
The purpose of this study is to investigate physicists’ views about the possible impacts of recent developments in quantum physics on educational implementations, particularly on science learning. Throughout the research a mixed-methods strategy was used. The data were collected from the physicists working at the European Organization for Nuclear Research (CERN). The qualitative and quantitative results were compared to portray the consistency between the two cohorts. The results indicated that the physicists’ experiences could provide valuable contributions to educational practices, and both teachers and students could benefit from the knowledge exchange between the field specialists. The implications for, and potential contributions to educational practices are discussed, taking into account the three most pertinent subfields, namely curriculum, learning, and teaching methods.